A Bibliometric Analysis of Sugar Beet for Production of Biofuels - JimÃ©nez-Islas, Donaji; PÃ©rez-Romero, Miriam Edith; Rivera-RÃos, Juan Manuel; Flores-Romero, Martha Beatriz (International Journal of Energy Economics and Policy, 2021)
The ongoing depletion of fossil resources, the energetic autonomy of countries, soaring prices for petroleum and climate change have stimulated research and development on renewable energy as biofuels. In this work, a bibliometric analysis of the Web of Science database was carried out to identify the research related to sugar beet to biofuels. The equation logistic was used to quantitatively describe the growth of the publication of sugar beet in the biofuels field. The results show that the publications of sugar beet for biofuel have a rate of growth of 0-1898 year-1. Germany and the USA were the countries with high influence for research in the field of sugar beet for biofuels. The journal Zuckerindustrie was the referent to publications in the field of study. From 2003 to 2019, the exponential growth of publications was found, this profile of growth can be attributed to the development of renewable energy and the relevance of global warming, security energetic and laws that promoted clean energy. This work shows that the logistic equation can be used to predict the evolution of publications in the field of study. Keywords: Beta vulgaris, beets, root beets, biofuel, fodder beet JEL Classifications: Q16, Q20, Q42 DOI: https://doi.org/10.32479/ijeep.11013